Experimental investigation on surface morphology and recasting layer of Si3N4-TiN composites machined by die-sinking and rotary EDM. Issue 5 (1st March 2023) - Selvarajan, L.; Rajavel, R.; Venkataramanan, K.; Srinivasan, V.P.
Abstract: Si3 N4 -TiN composites have extensive manufacturing applications because of their first-rate mechanical and thermal properties. Conversely, they are very demanding on machines that use conventional practices because of their superior strength and hardness. Electrical discharge machining is a viable substitute for machining of Si3 N4 -TiN composites through electrical erosion. However, very few studies have been conducted on the machinability and surface characteristics of electrical-discharge-machined composites. This study focuses on the materials processing characteristics of a Si3 N4 -TiNcomposite using rotary EDM and die-sinking EDM performed with a Cu electrode. In addition, the surface and cross section of the subsurface of the composite were examined, along with energy dispersive X-ray analysis, to identify the elements present on the machined surface. It was found that the high level of hardness and low level of toughness of the Si3 N4 -TiN composite contributed to the presence of microcracks, globules, pores, recast layers, and craters on the EDMed surface. The recast layer thicknesses of the die-sinking EDM (optimum hole, 106 μm; best hole, 151 μm; worst hole, 166 μm) and rotary EDM (optimum hole, 53 μm; best hole, 55 μm; and worst hole, 58 μm) were examined. In addition, the presence of pores and ablation increased significantly during the rotary EDM process. Rotary EDM parameters capable of producing a minimum white layer thickness were also investigated. Finally, the porosity levels were estimated according to the number of pores using ImageJ software. For the die-sinking EDM, the estimated porosity values for the optimum, best, and worst holes were 14.989%, 19.525%, and 21.706% respectively and for the rotary EDM, these values were 24.873%, 33.04%, and 37.99% respectively.